Low-Level Atmospheric Responses to the Sea Surface Temperature Fronts in the Chukchi and Bering Seas - Kawai, Yoshimi (Frontiers in Marine Science, 2021)
Atmospheric responses to ocean surface temperature (ST) fronts related to western boundary currents have been extensively analyzed over the last two decades. However, the organized near-surface response to ST, which is defined as the temperature of open water and sea ice, excluding land surface, at higher latitudes where sea ice exists has been rarely investigated due to the difficulties of observations. Here, 32 years of high-resolution atmospheric reanalysis data are analyzed to determine the atmospheric responses to ST fronts in the Bering Sea and Chukchi Sea. In the Chukchi Sea, the convergence of 10-m-high wind increases in October and November, when the horizontal gradient and Laplacian of ST become noticeable. On the other hand, an ST contrast between the continental shelf and the southwestern deep basin develops in winter in the Bering Sea. In both seas, the spatial distribution of surface wind convergence and the Laplacians of ST and sea level pressure agree well with each other, demonstrating the pressure adjustment mechanism. The vertical mixing mechanism is also confirmed in both seas. Ascending motion and diabatic heating develop over the Chukchi Sea in late autumn, but are confined to the lower troposphere. Turbulent heat fluxes at the surface become especially large in this season, resulting in an increase of diabatic heating and low-level clouds. Low-level clouds and downward shortwave radiation exhibit contrasting behavior across the shelf break in the Bering Sea that corresponds to the ST distribution, which is regulated by the bottom topography.